Placental Growth Measures in Relation to Birth Weight in a Latin American Population - Carlos Grandi; Angélica Veiga; Nancy Mazzitelli; Ricardo de Carvalho Cavalli; Viviane Cardoso (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Introduction The placenta, translates how the fetus experiences the maternal environment and is a principal influence on birth weight (BW). Objective To explore the relationship between placental growth measures (PGMs) and BW in a public maternity hospital. Methods Observational retrospective study of 870 singleton live born infants at Hospital Maternidad Sardá, Universidad de Buenos Aires, Argentina, between January 2011 and August 2012 with complete data of PGMs. Details of history, clinical and obstetrical maternal data, labor and delivery and neonatal outcome data, including placental measures derived from the records, were evaluated. The following manual measurements of the placenta according to standard methods were performed: placental weight (PW, g), larger and smaller diameters (cm), eccentricity, width (cm), shape, area (cm2), BW/PW ratio (BPR) and PW/BW ratio (PBR), and efficiency. Associations between BW and PGMs were examined using multiple linear regression. Results Birth weight was correlated with placental weight (R2 =0.49, p < 0.001), whereas gestational age was moderately correlated with placental weight (R2 =0.64, p < 0.001). By gestational age, there was a positive trend for PW and BPR, but an inverse relationship with PBR (p < 0.001). Placental weight alone accounted for 49% of birth weight variability (p < 0,001), whereas all PGMs accounted for 52% (p < 0,001). Combined, PGMs, maternal characteristics (parity, pre-eclampsia, tobacco use), gestational age and gender explained 77.8% of BW variations (p < 0,001). Among preterm births, 59% of BW variances were accounted for by PGMs, compared with 44% at term. All placental measures except BPR were consistently higher in females than in males, which was also not significant. Indices of placental efficiency showed weakly clinical relevance. Conclusions Reliable measures of placental growth estimate 53.6% of BW variances and project this outcome to a greater degree in preterm births than at term. These findings would contribute to the understanding of the maternal-placental programming of chronic diseases.